2010
DOI: 10.1038/nature09032
|View full text |Cite
|
Sign up to set email alerts
|

G domain dimerization controls dynamin's assembly-stimulated GTPase activity

Abstract: Dynamin is an atypical GTPase that catalyzes membrane fission during clathrin-mediated endocytosis. The mechanisms of dynamin’s basal and assembly-stimulated GTP hydrolysis are unknown, though both are indirectly influenced by the GTPase effector domain (GED). Here we present the 2.0Å resolution crystal structure of a minimal GTPase-GED fusion protein (GG) constructed from human dynamin 1, which has dimerized in the presence of the transition state mimic GDP.AlF4−. The structure reveals dynamin’s catalytic mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
427
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(451 citation statements)
references
References 50 publications
22
427
1
1
Order By: Relevance
“…[9][10][11] We observed an B20% reduction in patient fibroblasts with the p.Phe379Val mutation (Figure 2c). 10,11 As dynamin is a GTPase that can tubulate and sever membranes, 12,13 we measured the basal GTPase activity of wild-type and p.Phe379Val DNM2 recombinant proteins and found that the p.Phe379Val mutant's activity was reduced by 20% (Figure 2d). This mutant also failed to tubulate small unilammellar vesiscles in an in vitro assay (Figure 2e).…”
Section: Impact Of the Pphe379val Mutation On Dnm2 Functionmentioning
confidence: 99%
“…[9][10][11] We observed an B20% reduction in patient fibroblasts with the p.Phe379Val mutation (Figure 2c). 10,11 As dynamin is a GTPase that can tubulate and sever membranes, 12,13 we measured the basal GTPase activity of wild-type and p.Phe379Val DNM2 recombinant proteins and found that the p.Phe379Val mutant's activity was reduced by 20% (Figure 2d). This mutant also failed to tubulate small unilammellar vesiscles in an in vitro assay (Figure 2e).…”
Section: Impact Of the Pphe379val Mutation On Dnm2 Functionmentioning
confidence: 99%
“…7B). GTPase -GTPase contacts, stabilized by GTP binding (Chappie et al 2010), generate a very different twofold relationship, which coupled with the stem-dimer would produce a repeating polymer (Fig. 7C).…”
Section: Synaptojaninmentioning
confidence: 99%
“…In addition, GTPases of this family often depend on nucleotide-dependent homodimerization to facilitate GTP hydrolysis rather than heterodimerization with a GTPase activating protein (2). Such a regulatory mechanism has been established for guanylate-binding protein (GBP) and dynamin (3,4).…”
mentioning
confidence: 99%
“…In low-resolution models of dynamin, the middle domain and GED form a stalk-like structure that is involved in self-assembly (6,7). Furthermore, the GED and the C terminus of the G domain form a three-helix bundle, called the bundle signaling element (BSE), which modulates dynamin function (4,8). A recent crystal structure of a minimal G domain-GED fusion protein revealed dimeric G domains in a catalytically competent transition state that was proposed to play a role in the disassembly of dynamin coats from membrane tubes proceeding the fission event (4,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation